Enhancing food safety - Marques, Ana Paula (2024)
This study aimed to explore the use of ultraviolet-C light emitting diodes that emit light at 255 nm and 265 nm, to disinfect bacteria present at occurrence levels and spiked in water matrices, salads and stainless-steel surfaces. The UV-C LEDs effectively inactivated bacteria associated with food outbreaks (Salmonella enterica, Listeria monocytogenes and Escherichia coli) as well as a cocktail of bacteria isolated from packaged salads. Combining the wavelengths did not enhance disinfection. Even low UV fluences of 4 mJ/cm2 achieved a significant 6-log reduction of bacteria spiked in water at high initial concentrations of approximately 108 CFU/mL. Exposure of salad (lettuce and arugula) leaves (110 mJ/cm2) and contaminated stainless-steel surfaces (11 mJ/cm2) to three small LEDs that emit light at 265 nm reduced the pathogenic bacteria by 3 and 2-logs, respectively. The results obtained show that this disinfection technology could be promising for the food industry to guarantee effective inactivation of bacteria associated with foodborne diseases present in water, food and surfaces. Industrial relevance: This study demonstrated the potential of ultraviolet-C light emitting diodes, emitting at 255 nm and 265 nm, to provide an effective and sustainable disinfection solution for the food industry, ensuring the inactivation of bacteria associated with foodborne diseases on water, food, and surfaces, thereby enhancing food safety. Additionally, this technology holds potential for extending product shelf-life, further benefiting the food industry. The results highlighted the effectiveness of UV-C LEDs even at low fluences, making them a practical choice for modern disinfection needs.